The Internet communication in the perspective of personalism of E. Mounier - Więckowski, Robert (Studia Ecologiae et Bioethicae, 2003)
In the paper, it is discussed the communicative role of the Internet in the view of Mounier’s conception of personal communication. E. Mounier distinguishes two aspects of human communication: objective and subjective. The first one is reduced to the function of giving information, the second one. is specific for a man as a person. It is presented the most essential features of subjective, existential communication, that after all requires an understanding of other people. This attitude, according to Mounier, is not possible without opening to transcendence. In this view, the Internet is regarded as an objective tool of communication. It is briefly discussed the main ways of using the Internet in keeping up human relationships, the specific features of the tool, its advantages and disadvantages for personal contact. Finally, the development of the Internet is understood as a symptom of the need of passing on thoughts, considerations, and love to others as a human special privilege.